2022
DOI: 10.3390/ijms231911454
|View full text |Cite
|
Sign up to set email alerts
|

Two Conserved Amino Acids Characterized in the Island Domain Are Essential for the Biological Functions of Brassinolide Receptors

Abstract: Brassinosteroids (BRs) play important roles in plant growth and development, and BR perception is the pivotal process required to trigger BR signaling. In angiosperms, BR insensitive 1 (BRI1) is the essential BR receptor, because its mutants exhibit an extremely dwarf phenotype in Arabidopsis. Two other BR receptors, BRI1-like 1 (BRL1) and BRI1-like 3 (BRL3), are shown to be not indispensable. All BR receptors require an island domain (ID) responsible for BR perception. However, the biological functional signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Loss-of-function genetics has established BRI1 as the dominant Arabidopsis brassinosteroid receptor because it is essential for growth (Li and Chory, 1997, Li et al, 2022), whereas minor roles or specific functions were assigned to its homologs BRL1 and BRL3 (Cano-Delgado et al, 2004, Fabregas et al, 2018). In bri1 single mutants, BRL1 and BRL3 are presumably still active in stele tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Loss-of-function genetics has established BRI1 as the dominant Arabidopsis brassinosteroid receptor because it is essential for growth (Li and Chory, 1997, Li et al, 2022), whereas minor roles or specific functions were assigned to its homologs BRL1 and BRL3 (Cano-Delgado et al, 2004, Fabregas et al, 2018). In bri1 single mutants, BRL1 and BRL3 are presumably still active in stele tissues.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that two conserved amino acids Tyr597 and Tyr 599 are required by BRI1 for BR perception. Mutating these two amino acids in the ID abolished the BR signaling by knocking out or knocking down the phosphorylation activity of BES1 ( Li et al., 2022 ). Previous studies proved that the activation loop, αC helix, and αC-β4 loop are the most critical hotspots for kinase activation, and any abnormality in these regions can lead to the complete eradication of phosphorylation activity and cancer-related diseases in humans ( Taylor et al., 2012 ; Gogl et al., 2019 ; Yeung et al., 2020 ).…”
Section: Conserved Crystal Structure Of Rlks and Epksmentioning
confidence: 99%